Suicidal Ideation and Suicide Attempts among Women Seeking Treatment for Substance Use and Trauma Symptoms. Issue 2 (21st February 2018) - Resko, Stella M; Kruman Mountain, Sarah; Browne, Suzanne; Kondrat, David C; Kral, Michael
Abstract: Substance use disorders and posttraumatic stress disorder have been associated with suicide. Through secondary analysis of the screening data from the Women and Trauma Study conducted by the National Institute on Drug Abuse Clinical Trials Network, the present study examined rates and correlates of suicidal ideation and suicide attempts among women who sought treatment for substance use and trauma at seven outpatient substance use programs. The sample included women between the ages of 18 and 65 years ( M = 39.2; SD = 9.3) and was 44 percent white, 33 percent African American, 8 percent Latina, and 15 percent other races or ethnicities. Logistic regression was used to examine factors associated with a lifetime history of recurrent suicidal ideation and a serious suicide attempt. Findings highlight the need for social workers to address elevated risk levels for suicidal thoughts and behaviors when working with women with histories of substance use and trauma.